2018
DOI: 10.1128/aem.00745-18
|View full text |Cite
|
Sign up to set email alerts
|

A Repeating Sulfated Galactan Motif Resuscitates Dormant Micrococcus luteus Bacteria

Abstract: Only a small fraction of bacteria can autonomously initiate growth on agar plates. Nongrowing bacteria typically enter a metabolically inactive dormant state and require specific chemical trigger factors or signals to exit this state and to resume growth. has become a model organism for this important yet poorly understood phenomenon. Only a few resuscitation signals have been described to date, and all of them are produced endogenously by bacterial species. We report the discovery of a novel type of resuscita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 37 publications
1
2
0
Order By: Relevance
“…This hypothesis was supported by previous studies, in which Cordyceps cicadae polysaccharide was also believed to serve as nutrition for E• coli growth after 24 h cultivation [27,28]. However, according to recent studies, it is reported that sulfated galactans are required for growth of Gram-positive Micrococcus luteus [29]. Therefore, the effects of sulfated polysaccharide on different microorganisms remain to be further studied.…”
Section: Discussionsupporting
confidence: 55%
“…This hypothesis was supported by previous studies, in which Cordyceps cicadae polysaccharide was also believed to serve as nutrition for E• coli growth after 24 h cultivation [27,28]. However, according to recent studies, it is reported that sulfated galactans are required for growth of Gram-positive Micrococcus luteus [29]. Therefore, the effects of sulfated polysaccharide on different microorganisms remain to be further studied.…”
Section: Discussionsupporting
confidence: 55%
“…The history of knowledge of M. luteus could date back to 1922, when Fleming used it to prove the lytic activity of lysozyme found in body secretions and tissues [4,5]. Since then, M. luteus was gradually used in a variety of scienti c elds [6][7][8][9][10]. One of the most famous application is resuscitating and stimulating the protein called resuscitation-promoting factor (Rpf), which could promote the resuscitation and growth of some bacteria by autocrine and paracrine signalling functions (e.g., Mycobacterium, Arthrobacter, Bacillus, Streptomyces, etc) [14].…”
Section: Introductionmentioning
confidence: 99%
“…The collection and pretreatment of red algae E. serra and G. verrucosa were performed according to the methods used in an earlier study [ 18 ]. The sulfated galactans from E. serra were extracted and isolated based on previous studies [ 18 , 30 ]. Briefly, 100 g of the dried E. serra powder were macerated in water at 50 °C for 4 h. Then, the E. serra syrup was filtered through filter cloth, concentrated to 1/4th of the original volume, cooled, and precipitated overnight with three volumes of ethanol at 4 °C.…”
Section: Methodsmentioning
confidence: 99%